Ammonothermal Synthesis and Crystal Structure of BaAl2(NH2)8·2NH31. Issue 7 (18th April 2013) - Pust, Philipp; Schmiechen, Sebastian; Hintze, Frauke; Schnick, Wolfgang
Abstract BaAl2(NH2)8·2NH3 was synthesized starting from an intermetallic phase with nominal composition Al2Ba under ammonothermal conditions in a stainless‐steel autoclave at 823 K and 245 MPa. Single crystals were grown on aluminum substrates and prepared under low‐temperature conditions. The crystal structure (R <![CDATA[$\bar{3}$]]> <inline-graphic xlink:href="ark:/27927/pgg21msxq84" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c (no. 167), a = 15.7370(17), c = 28.804(6) Å, Z = 1, 1829 reflections, 65 parameters, wR2 = 0.07) was solved on the basis of single‐crystal X‐ray diffraction data. BaAl2(NH2)8·2NH3 contains isolated Al(NH2)4‐tetrahedra forming two different types of channels along [001].